KUALITAS AIR SUNGAI BELAWAN DI DESA LALANG KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA (Belawan River Water Quality in Lalang Village Deli Serdang Regency of North Sumatera) - Irma Shinta Roulia; Ternala Alexander Barus; Riri Ezraneti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Belawan River in Lalang Village is the river that contained domestic and market activity. The existence of dumping waste into rivers affecting water quality straight with the level of pollution generated. This study aims to determine the water quality of Belawan river in Lalang Village based on physic, chemical, and biology (makroozoobenthos) parameters. Physic and chemical parameters were analyzed by Storet method, while biological parameters (macrozoobenthos) were analyzed by Abudance and Biomass Comparison (ABC) curve. The study was conducted in January to February 2014. The method used Purposive Random Sampling. Stations are used Station 1 (control), station II (domestic activity), and station III (market activity). Physic and chemical parameters is temperature 26.33 − 29.00 °C, turbidity (TSS) 8.79 − 12.99 mg/L, DO 4.37 − 6.57 mg/L, pH 5.17 − 6.43, BOD 0.52 − 0.64 mg/L, nitrate 0.65 − 0.87 mg/L, phosphate 0.11 − 0.13 mg/L, abudance and biomass of makroozoobenthos: 0 − 88% and 0 − 87%. Based on physical and chemical parameters of water, the station I had score 0 which indicates the water quality is satisfying the quality standard (class I), whereas station II and III had score -10 which indicates water quality is mild contaminated (class II). Biological parameter (makroozoobenthos) produce overlapping curves that show the quality water is medium at each station.Keywords : Belawan River, Lalang Village, Macrozoobenthos, Water Quality